Studi Implementasi Directional Earth Fault Protection Pada Proteksi Bay Penghantar 150 KV Garuda Sakti - Teluk Lembu - Anggoro, Arief Sandy; Hamdani, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In order to optimize High Voltage Transmission Line Protection when a phase to ground fault occurs with high resistance value is implemented DEF (Directional Earth Fault) as protection feature on Distance Relay to detect this fault. Directional Earth Fault working method uses 3I0 residual neutral current detection related to zero order or negative sequence and 3V0 neutral voltage so that the DEF operation area is known both direction, minimum current and minimum voltages. High Voltage Transmission Line Protection in section 150 kV Garuda Sakti - Teluk Lembu is implemented DEF through stages of recording data collection of disturbances from previous conditions as reference of high-resistance ground phase conditions for comtrade playback record method, Simulation of transmission conditions and equipment during the disturbance conditions using Digsilent 14.0 study simulation for power system and short circuit circuit analiysis, application of relay protection protocol manufacturer Schneider type Micom P442, and simulation of individual testing using Omicron CMC 356. Each stages of DEF implementation of this study will be fulfilled when the results of simulation succed and final settings implementation on the protection relay with good individual test results.Keywords : DEF, High Resistance, Comtrade.